Thermally dynamic examination of local order in nanocrystalline hydroxyapatite - Arnold, Emily; Gosling, Sarah; Davies, Samantha K.; Cross, Hannah L.; Evans, Paul; Keeble, Dean S.; Greenwood, Charlene; Rogers, Keith (Elsevier, 2022)
The main mineral component of bone is hydroxyapatite, a commonly nanocrystalline material which presents many challenges for those trying to characterize it. Here, local structure is analyzed using X-ray total scattering for synthetic samples, to enable a better understanding of the nanocrystalline nature of hydroxyapatite. Two samples were measured dynamically during heat treatment from 25°C to 800°C, and were analyzed using small box modelling. Analysis of sequential measurements when dwelling at key temperatures showed a significant relationship between time and temperature, indicating a process occurring more slowly than thermal expansion. This indicates a decrease in B-type CO32- substitution between 550°C and 575°C and an increase in A-type CO32- substitution above 750°C. A greater understanding of local, intermediate, and long-range order of this complex biomineral during heat treatment can be of interest in several sectors, such as in forensic, biomedical and clinical settings for the study of implant coatings and bone diseases including osteoporosis and osteoarthritis.
Keywords: Hydroxyapatite; Powder X-ray Diffraction (PXRD); Total Scattering; Pair Distribution Function (PDF)